The Acute Pharmacological Manipulation of Dopamine Receptors Modulates Judgment Bias in Japanese Quail - Pichová, Katarína; Kubíková, Ľubica; Košťál, Ľubor (Frontiers in Physiology, 2022)
We have studied the effects of dopamine antagonists and agonists on Japanese quail behavior in the spatial judgment task. Twenty-four Japanese quail hens were trained in the spatial discrimination task to approach the feeder placed in the rewarded location (Go response, feeder containing mealworms) and to not approach the punished location (No-Go response, empty feeder plus aversive sound). In a subsequent spatial judgment task, the proportion of Go responses as well as approach latencies to rewarded, punished, and three ambiguous locations (near-positive, middle, near-negative, all neither rewarded nor punished) were assessed in 20 quail hens that successfully mastered the discrimination task. In Experiment 1, each bird received five treatments (0.1 and 1.0 mg/kg of dopamine D1 receptor antagonist SCH 23390, 0.05 and 0.5 mg/kg of dopamine D2 receptor antagonist haloperidol, and saline control) in a different order, according to a Latin square design. All drugs were administered intramuscularly 15 min before the spatial judgment test, with two days break between the treatments. Both antagonists caused a significant dose-dependent increase in the approach latencies as well as a decrease in the proportion of Go responses. In Experiment 2, with the design analogous to Experiment 1, the hens received again 5 treatments (1.0 and 10.0 mg/kg of dopamine D1 receptor agonist SKF 38393, 1.0 and 10.0 mg/kg of dopamine D2 receptor agonist bromocriptine, and saline control), applied intramuscularly 2 h before the test. The agonists did not have any significant effect on approach latencies and the proportion of Go responses in the spatial judgment task, as compared to the saline control, except for 10.0 mg/kg SKF 38393, which caused a decrease in the proportion of Go responses. The approach latency and the proportion of Go responses were affected by the cue location in both experiments. Our data suggest that the dopamine D1 and D2 receptor blockade leads to a decrease in the reward expectation and the negative judgment of stimuli. The effect of dopamine receptor activation is less clear. The results reveal that dopamine receptor manipulation alters the evaluation of the reward and punishment in the spatial judgment task.